Comparison of Local and Foreign Cultural Preferences Among Students of SMAN 1 Samarinda and its Implications for Cultural Learning - Nabila Maratus Sholihah (Green Publisher Indonesia, 2026)
Globalization and the rapid development of digital media have intensified adolescents’ exposure to foreign cultures, potentially affecting the sustainability of local culture and the effectiveness of cultural education in schools. This research aims to compare students’ preferences for local and foreign cultures at SMAN 1 Samarinda and to examine their implications for cultural learning. A quantitative approach with a descriptive-comparative survey design was employed. The participants consisted of 50 students selected through purposive sampling. Data were collected using a cultural literacy questionnaire covering cultural preferences, familiarity, participation, and attitudes toward local cultural preservation, and were analyzed using descriptive and simple comparative statistics. The findings reveal that students demonstrate higher preferences, familiarity, and participation toward foreign culture than local culture. However, students show positive attitudes toward the importance of preserving local culture, although this awareness is not fully reflected in active participation. These results indicate a gap between cultural awareness and preservation practices. The study concludes that students’ cultural preferences have significant pedagogical implications, suggesting that local cultural learning should be designed in a more contextual, adaptive, and experiential manner to enhance student engagement in the era of globalization.